Public development policies (Research, Society and Development, 2021)
With the end of World War II and the dynamics of the economy, countries entered the race to compete within the new globalized model. With this, an urban-industrial society has expanded, with politicized needs and needs that have become public issues, requiring greater State interventions, especially for integration into the new world economic order, emphasizing the need for public policies for development be more cohesive and egalitarian. Within this context, this article is a qualitative bibliographic exploratory research that aims to understand the need for public policies to promote development in Brazil, bringing important public actions in this process, such as the creation of superintendencies SUDENE, SUDECO, SUDESUL, SUDAM, as well as a basis for knowledge of terms such as: development, space, region, regional development and local development. The theoretical framework is structured in authors such as: Celso Furtado, Henri Lefebvre, David Harvey, among others that were found in the databases: Scopus, Web of Science and Scielo. As a result, it is understood that public policies have been discussed over the years, and are shown to be necessary, but there are still many improvements to be made.